UPAYA MENINGKATKAN MOTIVASI DAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN TIPE NUMBERED HEADS TOGHETHER SISWA KELAS VIII SMP N 1 ALIAN - Prihastini Oktasari Putri; Agustina Sri Purnami (UNION: Jurnal Ilmiah Pendidikan Matematika, 2014)
Theaimof thisresearchistoknowtheimprovingstudent’smotivation andtheoutcome inthefirstsemesterof2013/2014ofstudentVIII gradein SMPN1Alian,Kebumen usedcooperativelearning of Numbered Heads Together (NHT). This research is Classroom Action Research (CAR) conducted in two cycle. This research applied action researchwithcollaborativelearning,istheresearchercooperateswith teacher.The subjects of this research is students of class VIII D SMP N Alian Kebumen totaling 32 students. Data collection techniques in this research uses observation, questionnaires, and tests. Theresultof thisresearchcanbeconcludingasNumbered HeadsTogether(NHT)canimprovemotivation and thestudent’s outcome of study in SMP N 1 Alian, Kebumen. Theusingof cooperative learningtypeNumberedHeadsTogether(NHT)andtheresultsof the studyingisimprovedusedinVIIIgradestudentof SMPN1Alian, Kebumen.